AI Remote Monitoring vs. Hospital Stays: Bridging the Digital Divide in Healthcare - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The landscape of healthcare is undergoing a profound transformation, driven by the convergence of Artificial Intelligence AI and digital health technologies....
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Wearable Technology